Inisiasi Penguatan Kemampuan Literasi dan Numerasi Siswa Sekolah Dasar melalui Program Literasi Berbasis Rumah - Rochaendi, Endi; Ma’mun, Saepul; Supriadi, Asim; Hardianto, Deni (Alma Ata University Press, 2025)
The decline in literacy and numeracy achievement among primary school students across various regions, including Majalengka Regency, underscores the urgent need for educational interventions that transcend conventional institutional approaches and emphasize cross-contextual learning collaboration. This article critically examines the potential of the Home-Based Literacy Program as an alternative strategy to not only strengthen students’ foundational competencies but also accelerate the realization of the six dimensions of the Pancasila Student Profile. Employing a literature review method, the study consolidates and analyzes recent scholarly works related to parental involvement, digital literacy development, and the integration of character values within the domestic learning environment. Findings indicate that home-based literacy, when supported by contextually relevant instructional design, functional school-family synergy, and sustained policy backing, significantly enhances literacy and numeracy skills while fostering values such as independence, collaboration, critical reasoning, and creativity. Furthermore, digital literacy integration and sensitivity to local cultural diversity emerge as critical determinants of program efficacy and social acceptability. The study concludes that home-based literacy represents a transformative, ecosystem-driven initiative with strong potential for broad contextual replication and serves as a strategic foundation for the reformulation of inclusive, participatory, and equitable educational policy.